Literatur Review : Rapid Immunochromatography Sebagai Metode Skrining Kanker Serviks Berbasis Deteksi Onkoprotein HPV pada Urin - Ika Rahmawati Sutejo; Kiky Martha Arieska (Jurnal Kesehatan, 2020)
Cervical cancer is still become main health problem especially in development country. This cancer is the second most common cancer in Indonesian women. It commonly caused by infection of Human Papillomavirus (HPV) type 16 and 18. Actually if cervical cancer was detected earlier, it shows better respond therapy than other cancers, but this opportunity is not supported by appropiate screening methods. Nowadays, pap smear and IVA are commonly used for detect cervical cancer but they only recommend for women who have had sexual intercourse. Both of them also require medical expertise and pap smear is highly cost. Based on these problem, this paper describes novel method for cervical cancer screening by using rapid immunochromatography kit which is more applicative, noninvasive, and affordable. This paper was a literature review (library research). Data obtained through the search engine using keywords: "Cervical Cancer", "HPV", "Urine", "Screening", “Lateral flow test”, and "Rapid immunochromatography". The references were taken from reliable journal in the range of 2009 to 2019. Data was also taken from textbooks and the health institution official sites which support the analysis. This method detect the presence of oncoprotein E6 & E7 of HPV-16 and HPV-18 in urinusing antigen-antibody binding principle. Sensitivity and specificity test done by comparing the results of the kit with the results of pap smear tests as a standard screening method and PCR HPV test on urinsamples. We conclude that with further protocol development and standardization to achieve clinical sensitivity, this kit is a solution for noninvasive detection of high risk cervical cancer so that treatment can be do immediately and the mortality rate due to cervical cancer can be reduced as much as possible.